Social And Health Related Effects of Smart Phone Usage Among University Students - Junaid Tariq; Ambreen Usmani; Maroosha Imran; Naveed Faraz (Journal of Bahria University Medical and Dental College)
Objective: To assess the social and health related effects of smart phone usage among the students of a public university in Karachi. Study Design and Setting: Cross sectional study conducted on students of a public university of Karachi from July 2018 to October 2018 Methodology: A research questionnaire was distributed among students of a public university in Karachi. This anonymous questionnaire addressed the perceptions of the university students regarding usage of smart phones and its effects on health and social life. A total of 150 students were included in the study. The variable checked were effects on eyesight, whether the students feel relaxed or suffered from depression, experiences of headache, the effect on the students’ studies and family issues. Data was entered in SPSS version 23 and frequencies were calculated. Chi-square was applied on each variable and p-value less than 0.05 was considered significant. Result: One hundred and fifty students participated, of which 75 were females and 75 were males. It was observed those females were using WhatsApp more than their male counterparts. Males showed a slightly higher frequency of using Facebook and other internet Apps. From the total sample 66.6% noticed decrease in their eye sight, 17% are depressed, 38% had headache, 42% had bad effects on their studies and 43% had family related issues due to usage of smart phone Conclusion: Use of smart phone has many adverse effects on university students like poor eye sight, depression, headaches, effects on studies and family issues.